Perbandingan Persepsi pada Material Upcycle Do It Yourself (DIY) dengan Pendekatan Material Driven Design - Devanny Gumulya (JURNAL RUPA, 2019)
In the past five years, technology advances and fabrication feasibility like 3D printing has boost the do it your self-movement, and it is expanding beyond products to the materials that are labelled as DIY-materials. DIY- materials are created through individual or collective through self-production practices that involve a lot of creativity and innovative approach. One of these DIY-materials is upcycle-material. The pollution on landfill and ocean has encouraged us to be more responsible for the waste we create by recycling the waste and make it as new material. Eggshells and LPDE plastic bag waste are discussed in this paper. The perception between the two DIY-materials upcycle is compared using the material driven design approach (MDD). In MDD, sensorial, interpretation, affective and performative dimensions shape people’s perception and experience toward the materials. This approach is needed, to give waste material a new life and for it to be accepted on the market. Results from studies are the do and don’ts for product design process using eggshells and LDPE plastic bag waste. Imperfections through pattern, texture and colour are the qualities that people seek when interacting with DIY-upcycle materials. These qualities cannot be found in mass-produced industrial made material. Design principle such as balance, contrast, emphasis, movement, pattern, rhythm, and unity/variety needs to be well planned in making pattern, texture and colour because if it is done wrong, the material will be perceived back as waste.